Hubungan Antara Motivasi Berprestasi Dengan Kepercayaan Diri Pada Atlet Beladiri - Muriawijaya, Novenna Citrasari, Achmad Dwityanto, S.Psi, M.Si (2017)
From the results of interviews was researcher would request how do you feel while for the? a game must be in it there are athletes who is considered to be more the people of than other athletes and it makes other athletes feel hesitant and fear lest later when play meet the athletes and athletes who is considered to be more the people of is sometimes the experience similar fear the decline in their names.Researchers also interviewed coach fighter that the results of interviews with questions when athletes are in a game things anything that affects achievement the athlete? , an athlete who will be up to be ready to mental and techniques while for the, when play an athlete must trust yourself whether entered the arena the game and when meeting opposed to before play. An athlete who have confidence strong will not think "i can not" but an athlete who have confidence strong will think "i can fight it" .An athlete who have confidence good must be mental also good and will play well when play because they felt ready by applying a technique athletes have .Research aims to understand the whereabouts of relations motivation their achievement confidence in an athlete fighter city surakarta .The research is research correlation .The subject of study this is an athlete fighter who had once followed at least the game the provincial level which were 100 people .An instrument used in his research is the scale to know motivation their achievement confidence.This research purpose is to determine whether or nor there is relationship between motivation to get achievement and confidence on martial-arts athletes of Surakarta. This research is correlational research. The participants of this research are martial-arts athletes who have competed in provincial-level match that of one hundred people. The instrument which is usd in this research is the scale to determine motivation to get achievement and confidence. As for the method used to analyze the data is quantitative method. The result of this research is hypothesis testing which used the product moment correlation. Result= 0,825with P= 0,00 (P<0,01) showed that there is significantly positive relationship between confidence and motivation to get achievement. The motivation representatives indicated analysis of test motivation representatives have empirical rerata of 68,79 and rerata hypothetic of 52,5 showing motivation representatives high .It can be drawn the conclusion that outstanding fighter motivation athletes high . The confidence of high shown test motivation analysis representatives have empirical rerata of 84,14 and rerata hypothetic of 62,5 showing confidence high .It can be drawn the conclusion that confidence athletes high fighter .Contributions effective motivation representatives of confidence of 68,3 % .Means there are still 31,7 % other variables affecting confidence out the motivation achievement Keywords: motivation to get achievement, confidence, athletes.